Drawing a Boundary between Structural Factors and Identity in Ethnic Conflict: Bringing Back the Role of Identity - Abushov, Kavus (Terrorism and political violence, 2022)
This article focuses on the causes of ethnic civil wars, and argues that in order to develop a better understanding of their onset and intractability, one needs to distinguish different types of ethnic civil wars from each other. It first evaluates structural factors in the outbreak of ethnic conflict and then proceeds to discuss ideational factors and finally suggests a theoretic framework of understanding ethnic conflict based upon identity. It develops hypotheses that would allow to discern structuralist explanations from ideational ones and in this way contributes to the literature that tries to understand the causes of ethnic civil wars. To have a clear understanding of the suggested hypotheses, empirical evidence is provided from the post-Soviet space, namely conflicts such as Abkhazia, Crimea, Chechnya, Nagorno-Karabakh, and South Ossetia.